Service Quality Agriculture Counseling and Satisfaction Farmers in Farming Development (Case Study on VegetableiFarmers in Nania Village, Baguala District, Ambon City) - Talia F Mayaut; Aphrodithe M Sahusilawame; Melvis E Tahitu (Universitas Pattimura, 2023)
Development goals in Indonesia have existed for a long time, with the main objective of prioritizing the agricultural sector and increasing agricultural welfare. Through extension activities which are a series of ongoing processes according to the needs of farmers. The presence of agricultural extension workers as the spearhead of implementing agricultural development. Improving the performance of agricultural extension agents also determines future agricultural development, which determines the income of the agricultural sector. Good service quality is a determinant of the success of agricultural development. This study aimed to assess the quality of agricultural extension services and farmers' satisfaction level in developing vegetable farming in Nania Village. This research was conducted in Nania Village from November 2022 to December 2022. The type of research used was census research. The total population in this study was 16 people, all of whom were vegetable farmers in the village of Nania. The sample in this study was the entire population. The type of data collected includes primary data and secondary data. The data analysis technique used is descriptive qualitative data analysis. The results showed that the quality of counseling services on indicators of counseling preparation was in the medium category with an average (2.30), the implementation of counseling was in the medium category (2.15), and the appropriateness of the counseling method (2.49) was in the high category. While the level of farmer satisfaction with agricultural extension services, seen from the accuracy of the service, is classified as medium (2.2), and the performance of extension workers are classified as high or very good with an average (2.65). The conclusion is that the quality of agricultural extension services in Nania Village is in the moderate or adequate category. And the level of farmer satisfaction with extension services is classified as medium and high categories.